Language and the (re)production of dominance: Zimbabwe African National Union-Patriotic Front (ZANU-PF) advertisements for the July 2013 elections - Chibuwe, Albert (Critical Arts, 2020)
Language is a political tool used to legitimise, delegitimise, produce and (re)produce dominance. In Zimbabwe, ZANU-PF advertisements for the July 2013 elections were an attempt to deploy language to (re)produce dominance. The advertisements were produced in the context of a power-sharing government comprising ZANU-PF and the MDCs. Adopting sign theory, the article uses legitimation analysis to explore the ways in which ZANU-PF used language to retain dominance. Research revealed that ZANU-PF legitimated its dominance on the basis of performance, for example, implementing the multiple currencies system after the Zimbabwe dollar’s collapse and delivering a constitution that guarantees the values espoused by the liberation struggle. Mugabe’s incomparable “wisdom and deftness” in handling matters of state, ZANU-PF’s care for ordinary urban ratepayers and economic indigenisation were used to justify the party’s dominance. It also legitimised its rule by portraying the MDC-T as an uncaring, dishonest and sell-out party, thus delegitimising it while skilfully concealing its own blame in the collapse of the economy post-2000.